Versions multiples et langues en Europe - Martin Barnier (Mise au Point, 2013)
This article will examine the issue of the little-known multiple version production system which is an essential part of the European languages question. In this system a picture is filmed several times with actors from different countries playing in their native language. This process was first developed in the 1930’s with the advent of talkies. The fact that continental European audiences did not want to see English-only talking movies coupled with a political and economic anti-americanism help to explain these productions. To meet this challenge Paramount set up studios in Paris to shoot European versions of its films. But the most successful movies were the European productions themselves. From the Neubabelsberg studios in Berlin came the sound of operettas and comedy thrillers. Many famous actors, actresses, directors or scriptwriters received their training in these multiple versions (Pagnol, Gabin, Fernandel, Annabella) which stopped production during WW2. This article will then go on to study multilingual film versions from the 1950s and 1960s. Indeed the European co-productions facilitated the return of these films. One of the actors or actresses changes according to his/her fame in his/her country. These new multiple versions mix retakes (with different actors) and dubbing. Up until the end of the 1960s these films still existed and were made by filmmakers like Jacques Deray, Jacques Demy or Orson Welles.